Understanding user perspectives of and preferences for oral PrEP for HIV prevention in the context of intervention scale‐up: a synthesis of evidence from sub‐Saharan Africa. (22nd July 2019) - Eakle, Robyn; Weatherburn, Peter; Bourne, Adam
Abstract: Introduction: Oral pre‐exposure prophylaxis (PrEP) for HIV prevention has been proven to significantly reduce new HIV infections yet scale‐up has been slow. As contexts continue to adjust to make space for PrEP, it is crucial to understand the perspectives and experiences of potential end‐users. In order to inform PrEP and demand creation interventions, this paper examines personal perspectives on adopting and using PrEP among HIV at‐risk populations in sub‐Saharan Africa. Methods: Using the principles of a scoping review in July 2018, we explored the extent, range, and nature of published literature regarding PrEP uptake and use among; men who have sex with men, HIV serodiscordant couples, adolescent girls and young women, pregnant and breastfeeding women, women partners of migrant workers; and people who use drugs. Steps included: identification of the research question; identification of relevant studies; study selection; charting the data; and collation – summarizing and reporting results. PubMed and PsycInfo were searched for papers relating to PrEP uptake and use in sub‐Saharan Africa. Resulting papers were reviewed with data extracted and compiled in Excel for analysis. A broad content analysis was conducted and organized into high‐level themes. Results and discussion: Thirty‐five papers were included in this review. There was little opposition in general to oral PrEP; however, there were significant nuances in its broader acceptability, applicability, and usability. We identified five themes within which these are discussed. These relate to balancing complexities of personal empowerment and stigma; navigating complex risk environments; influences of relationships and partners; efficacy and side effects; and practicalities of use. This body of research suggests that while product attributes and the logistics of PrEP delivery and use are important topics, it is vital to consider stigma, the interactions of PrEP use with relationships, and the need for broader understanding of ARVs for prevention versus treatment. Conclusions: Planning for, programming and promoting the adoption of oral PrEP necessitates a deeper understanding of end‐user priorities in order to ensure successful interventions. This review illustrates the nuances facilitating or deterring PrEP use that may affect the larger effort of PrEP scale‐up.